2017
DOI: 10.1038/s41598-017-05574-9
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic increases in blood glutamate concentrations are closely related to traumatic brain injury-induced acute lung injury

Abstract: Traumatic brain injury-induced acute lung injury (TBI-ALI) is a serious complication after brain injury for which predictive factors are lacking. In this study, we found significantly elevated blood glutamate concentrations in patients with TBI or multiple peripheral trauma (MPT), and patients with more severe injuries showed higher blood glutamate concentrations and longer durations of elevated levels. Although the increase in amplitude was similar between the two groups, the duration was longer in the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…It is known that the concentration of glutamate in blood is~50-100 µM, whereas the extracellular levels of glutamate in the tissues are considerably lower (<1 µM). [32][33][34] Our data suggest that MC activation was triggered at glutamate concentrations ≥10 µM. It is thus reasonable to assume that the baseline concentration of extracellular glutamate in tissues is below this level.…”
Section: Discussionmentioning
confidence: 76%
“…It is known that the concentration of glutamate in blood is~50-100 µM, whereas the extracellular levels of glutamate in the tissues are considerably lower (<1 µM). [32][33][34] Our data suggest that MC activation was triggered at glutamate concentrations ≥10 µM. It is thus reasonable to assume that the baseline concentration of extracellular glutamate in tissues is below this level.…”
Section: Discussionmentioning
confidence: 76%
“…However, the effect of elevated blood glutamate on the concentration of intraparenchymal glutamate and whether it is also an important source of the rapid increase in intraparenchymal glutamate remain poorly understood. Moreover, while there is no direct evidence showing that intraparenchymal glutamate levels influence blood glutamate levels, the results of our recent studies in patients with TBI indicate that the severity of brain injury is positively associated with blood glutamate levels ( Bai et al, 2017 ).…”
Section: The Interrelationship Between Intraparenchymal and Blood Glumentioning
confidence: 84%
“…The glutamate concentration in the blood of healthy adults ranges from 40 to 60 μM ( Bai et al, 2017 ). In some in vitro studies using acute brain slices, extracellular glutamate ranges from 25 to 90 nM ( Cavelier and Attwell, 2005 ; Herman and Jahr, 2007 ; Le Meur et al, 2007 ); however, most in vivo studies using microdialysis, which is an FDA-approved method for clinical application, found much higher glutamate levels in brain, ranging from 0.2 μM to approximately 20 μM ( Dash et al, 2009 ; De Bundel et al, 2011 ).…”
Section: The Formation and Maintenance Of A Normal Intraparenchymal- mentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, glutamate concentrations were measured in blood samples using high-performance liquid chromatography (HPLC) [17,18]. While blood sampling is more invasive than imaging, the approach is still suitable for use in patients, and HPLC is reliable and sensitive enough to measure glutamate concentrations in blood samples, as well as in brain samples [17,19,20].…”
Section: Introductionmentioning
confidence: 99%